Mechanical and physical properties of chitosan film incorporated with plant oils - Nistion, Nur Afiqah; Zainal Abidin, Munira (Enhanced Knowledge in Sciences and Technology, 2023)
Chitosan is notable for its biodegradability, film forming and non-toxicity properties that extracted from shrimp’s exoskeletons and other crustaceans. Chitosan film have high in water vapor transmission rate (WVTR) and low tensile strength. This research was conducted to prepare edible film with incorporation of plant oils that are olive oil and lemon essential oil (LO) and analyses the mechanical and physical properties of the films. Different types of plant oils (OO and LO) were incorporated with chitosan film to study its effects on mechanical and physical properties. Variation in chitosan films produced using casting method on petri dish and dried in drying oven for 18 hours. Film samples characterization analyzed for color, opacity, film solubility, WVTR, water vapor permeability (WVP), tensile stress, elongation and FTIR spectrum. Chitosan film incorporated with olive oil (COO) has greenish color while chitosan film incorporated with lemon essential oil (CLO) was more yellow color than pure chitosan film (CS). Film opacity of COO and CLO increases with concentration. Film solubility decreases when concentration of oils increases. The WVTR and WVP of COO and CLO decreases with increasing oils concentration. Tensile stress of CLO increases as concentration increased. Elongation of COO decreases while elongation of CLO increases when increased in concentration of oils. FTIR analysis was done to determine bonds and functional groups presence in CS, COO and CLO. Through the analyses, incorporation of plant oils has enhanced the WVTR and tensile strength of chitosan film.